Capacity of the terrestrial entomopathogenic nematode Steinernema rarum (Rhabditida: Steinernematidae) to parasite Culex apicinus larvae (Diptera: Culicidae) - Cagnolo, Susana Raquel (2010)
Entomopathogenic nematodes can be considered as effective agents for biocontrol, resulting innocuous for humans. Culex apicinus larvae were exposed to infective juveniles of Steinernema rarum (OLI strain) under laboratory conditions, testing six dose (1:1, 5:1, 10:1, 15:1, 100:1, 400:1). An increasing percentage of mosquito larva mortality was recorded with increasing dose. The highest mosquito larva mortality (75%) was obtained with the dose 400:1. This is the first report of parasitism of S. rarum from Córdoba against larvae of Culex apicinus with promising results. Therefore, further studies must be carried out to evaluate these nematodes as possible autochthonous agents for the control of Culex mosquitoes and others of sanitary interest in the Country.